2014
DOI: 10.4141/cjas-2014-086
|View full text |Cite
|
Sign up to set email alerts
|

Fiber degradability, chemical composition and conservation characteristics of alfalfa haylage ensiled with exogenous fibrolytic enzymes and a ferulic acid esterase-producing inoculant

Abstract: 2014. Fiber degradability, chemical composition and conservation characteristics of alfalfa haylage ensiled with exogenous fibrolytic enzymes and a ferulic acid esterase-producing inoculant. Can. J. Anim. Sci. 94: 697Á704. This study investigated the effects of two fibrolytic enzyme products, applied at baling alone or in combination with a ferulic acid esterase-producing bacterial additive, on the ensilage dynamics, chemical composition and digestibility of alfalfa haylage. Five replicate wrapped bales were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…This might support that inoculation of FD and FDest decreased NDF concentration of rye silage in the present study. In agreement, Lynch et al [6] also reported that NDF concentration of alfalfa silage was lower in mixture of cellulase and xylanase treatment than that of control (32.1% vs 33.5%). Silage inoculated with FD increased both IVDMD and IVNDFD of rye silage in the present study.…”
Section: Con At At-m Fd Fd-est Con Vs At Vs Fd At Vs At-m Fd Vs Fd-estsupporting
confidence: 74%
See 1 more Smart Citation
“…This might support that inoculation of FD and FDest decreased NDF concentration of rye silage in the present study. In agreement, Lynch et al [6] also reported that NDF concentration of alfalfa silage was lower in mixture of cellulase and xylanase treatment than that of control (32.1% vs 33.5%). Silage inoculated with FD increased both IVDMD and IVNDFD of rye silage in the present study.…”
Section: Con At At-m Fd Fd-est Con Vs At Vs Fd At Vs At-m Fd Vs Fd-estsupporting
confidence: 74%
“…Application of lactic acid bacteria (LAB) in silage has been widely used to improve the fermentation quality [5] and digestibility of silage [6,7]. Several strains of LAB have abilities of producing antifungal [8,9] and fibrinolytic enzymes [9,10], which could increase the quality of rye silage, especially harvested at the dough stage.…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic and hydroxycinnamic acids themselves can promote health in animals [148, 149]; however, feruloylation in plant cell walls particularly in a high forage diet is among the major inhibitory factors for the ruminant digestive system. Addition of FAEs or enzyme cocktails containing FAEs can improve the access of main chain degrading enzymes resulting in improved fiber digestion and bioavailability of phytonutrients, accelerating animal growth (e.g., [150, 151]), as well as reducing immunological stress [152]. …”
Section: Industrial Applications Of Faesmentioning
confidence: 99%
“…FAE-producing LAB makes cross-linked polysaccharides more fragile and thus more easily degraded by rumen due to the synergy between esterases and main-chain degrading enzymes [ 10 ]. Several research studies have attempted to study the effects of FAE-producing LAB strains on ensiling and fiber degradability, and some of the findings have shown that LAB-treated silage exhibits higher neutral detergent fiber digestibility (NDFD) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%